The Rise of E-Commerce: Manus AI Powered Product Generation Before Sales Execution - Dita Helmalia Suri; Nava Gia Ginasta; Rahma Hanum (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Manus AI, an autonomous AI agent introduced in 2025, enables fashion businesses to generate product visualizations before physical production, supporting the sell-it-before-you-make-it approach. This study evaluates the implementation of Manus AI in pre-production fashion product development for e-commerce. A quantitative descriptive-explanatory approach was employed using two datasets: a survey of 70 fashion MSME owners to assess AI awareness and an evaluation of Manus AI-generated visualizations by 88 respondents using a five-point Likert scale. The results show that 58.6% of MSME owners had no prior knowledge of AI, indicating limited AI readiness. However, the visualizations generated by Manus AI were positively evaluated, with all indicators rated Good to Very Good (mean = 3.80–4.30). Respondents perceived that Manus AI produced realistic and market-oriented visualizations that support product validation before production while reducing prototype costs, development time, and material waste. These findings demonstrate that Manus AI can support more efficient and sustainable product development while emphasizing the importance of improving AI literacy among fashion MSMEs.